Colonial exchanges : Political theory and the agency of the colonized - Hendrix, Burke A.; Baumgold, Deborah (Manchester University Press, 2017)
Scholars of political thought have given a great deal of attention to the relationship between European political ideas and colonialism, especially to whether prominent thinkers supported or opposed colonialism. But little attention has so far been given to the reactions of those in the colonies to European ideas, where intellectuals actively sought to transform those ideas, deploying them strategically or adopting them as their own. A full reckoning of colonialism's effects requires attention to their intellectual choices and the political efforts that accompanied them, which sometimes produced surprising political successes. The contributors to this volume include a mix of political theorists and intellectual historians who seek to grapple with specific thinkers or contexts. Contributors focus on colonised societies including India, Haiti, the Philippines, Egypt, Morocco, Nigeria, and the settler countries of North America and Oceana, in times ranging from the French Revolution to the modern day.